2019
DOI: 10.1111/jeb.13557
|View full text |Cite
|
Sign up to set email alerts
|

The skull evolution of oviraptorosaurian dinosaurs: the role of niche partitioning in diversification

Abstract: Oviraptorosaurs are bird‐like theropod dinosaurs that thrived in the final pre‐extinction ecosystems during the latest Cretaceous, and the beaked, toothless skulls of derived species are regarded as some of the most peculiar among dinosaurs. Their aberrant morphologies are hypothesized to have been caused by rapid evolution triggered by an ecological/biological driver, but little is known about how their skull shapes and functional abilities diversified. Here, we use quantitative techniques to study oviraptoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 51 publications
3
24
0
Order By: Relevance
“…the Dinosaur Park and Horseshoe Canyon Formations), taxa in these ecosystems are highly disparate in morphology and body size [ 29 , 33 ]. Indeed, several studies have suggested that high oviraptorosaur diversity in several ecosystems was the result of morphological niche segregation [ 14 , 15 , 33 , 58 ]. Considering the low likelihood of this coexistence scenario and the lack of positive evidence for two morphotypes, “ Nomingia gobiensis” is best regarded as junior subjective synonym of Elmisaurus rarus .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the Dinosaur Park and Horseshoe Canyon Formations), taxa in these ecosystems are highly disparate in morphology and body size [ 29 , 33 ]. Indeed, several studies have suggested that high oviraptorosaur diversity in several ecosystems was the result of morphological niche segregation [ 14 , 15 , 33 , 58 ]. Considering the low likelihood of this coexistence scenario and the lack of positive evidence for two morphotypes, “ Nomingia gobiensis” is best regarded as junior subjective synonym of Elmisaurus rarus .…”
Section: Discussionmentioning
confidence: 99%
“…the Dinosaur Park and Horseshoe Canyon Formations), taxa in these ecosystems are highly disparate in morphology and body size [29,33]. Indeed, several studies have suggested that high oviraptorosaur diversity in several ecosystems was the result of morphological niche segregation [14,15,33,58]. Considering the low likelihood of this…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…However, the potential role of the forelimb in niche partitioning has not been previously recognized. Differences in forelimb morphology between caenagnathids and oviraptorids in the Nemegt Basin [33,47,115] may be the result of broader dietary differences already recognized on the basis of the mandibles [110]. Forelimb adaptability could also have contributed to the coexistence of citipatines and heyuannines in the same areas, as the skulls and mandibles of these taxa occupy similar morphospaces [110].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, current evidence suggests that all three caenagnathid taxa coexisted in the DPF, rather than constituting an anagenic lineage or a series of sequential forms replaced in association with faunal turnover. Considering the apparently highly specialized niche that oviraptorosaurs occupied relative to other theropods Ma et al 2020), some evidence of resource partitioning might be expected where species richness is relatively high, as is the case in the DPF. The variation in adult body sizes between each taxon may have facilitated the use of different resources later in life, and may have contributed to feeding height stratification , although this is untestable with currently known material and it is unclear what proportion of the caenagnathid diet comprised plant material.…”
Section: Ecology Of Dpf Caenagnathidsmentioning
confidence: 99%